Street trade and requalification of public spaces in Salvador-BA: a research agenda - Serpa, Angelo (Geografares, 2018)
The aim of this paper is to analyze the relationship between street trade and requalification processes in public spaces based on a geographical approach to the problem. It is intended to pursue and, therefore, make explicit the tactics and strategies of the agents involved in those projects and their trajectories and practices in the everyday life of the metropolis. We hope to outline the conjunctural contexts of the existing conflicts too, which are related to street traders and service providers, as opposed to the actions of the hegemonic agents of production of the metropolitan space and to the processes of requalification/refunctionalization of public spaces in the capital of Bahia state - Salvador, from the late 1990s to the present day.Keywords: street trade; street services; public space; requalification; territorialization; metropolis.